2010
DOI: 10.17925/ee.2013.09.01.21
|View full text |Cite
|
Sign up to set email alerts
|

Future Perspectives in Glucose Monitoring Sensors

Abstract: The prevalence of diabetes is increasing. Improved glucose control is fundamental to reduce both long-term micro- and macrovascular complications and short-term complications, such as diabetic ketoacidosis and severe hypoglycemia. Frequent blood glucose monitoring is an essential part of diabetes management. However, almost all available blood glucose monitoring devices are invasive. This determines a reduced patient compliance, which in turn reflects negatively on glucose control. Therefore, there is a need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The major difference observed in hypertension trends between these previous studies and the present study may be explained by the fact that the presence or absence of antihypertensive drug use could not be taken into account in our definition of hypertension due to insufficient data in the present study. The declining trend of hypertension risk observed in this study may reflect that although there was an increase in the number of people requiring antihypertensive treatment after the accident, as pointed out in previous studies [ 16 , 17 , 51–55 , 57 , 58 , 59 , 60 ], the blood pressure of those people was well controlled. In fact, adequate control of hypertension is possible because blood pressure can be monitored daily using a home sphygmomanometer after a disaster [ 61 ].…”
Section: Discussionsupporting
confidence: 69%
“…The major difference observed in hypertension trends between these previous studies and the present study may be explained by the fact that the presence or absence of antihypertensive drug use could not be taken into account in our definition of hypertension due to insufficient data in the present study. The declining trend of hypertension risk observed in this study may reflect that although there was an increase in the number of people requiring antihypertensive treatment after the accident, as pointed out in previous studies [ 16 , 17 , 51–55 , 57 , 58 , 59 , 60 ], the blood pressure of those people was well controlled. In fact, adequate control of hypertension is possible because blood pressure can be monitored daily using a home sphygmomanometer after a disaster [ 61 ].…”
Section: Discussionsupporting
confidence: 69%
“…50 In contrast, diabetes and hyperlipidaemia are more difficult to control after a disaster; almost all available blood glucose and cholesterol monitoring require invasive procedures, selfmonitoring is less accepted by patients, resulting in reduced patient compliance in diabetes and hyperlipidaemia monitoring and treatment. 51 Previous studies have reported associations between experiences of lifethreatening disaster and reduced chronic health control. 41 The findings of our study show that, regardless of evacuation, there was significantly increased risk of diabetes and hyperlipidaemia more than 3 years after Figure 2 Box plots for the distribution of radiation levels at non-evacuees'/temporary-evacuees' residences by disease status.…”
Section: Discussionmentioning
confidence: 99%
“…1 Self-monitoring of blood glucose limitations are infection risk, and it implies a significant number of daily punctures that are uncomfortable and painful. 3 Another method to obtain glucose measurements is continuous glucose monitoring (CGM). This technology uses a sensor, a glucose oxidase platinum electrode that generates an electrical current generating an average glucose value every 5 minutes in the presence of glucose.…”
Section: Aspects To Consider When Using Rs For Noninvasive Glucose Me...mentioning
confidence: 99%
“…2 Current, GM devices are invasive or minimally invasive, which need a significant number of daily punctures that are uncomfortable, painful, and pose an infection risk. 3,4 Also, they can be costly and uncomfortable to wear. 5 The above limitations explain why people with diabetes do not monitor their glucose levels as often as recommended.…”
Section: Introductionmentioning
confidence: 99%